2013
DOI: 10.1590/s1413-70542013000300002
|View full text |Cite
|
Sign up to set email alerts
|

Biomass production, yield and chemical composition of peppermint essential oil using different organic fertilizer sources

Abstract: Mentha x piperita L. is an aromatic and medicinal species belonging to the family Lamiaceae that is popularly known as peppermint. The aim of this study was to evaluate the effects of organic fertilizer sources on the biomass production, yield and chemical composition of peppermint (Mentha piperita L.) essential oil. The experiment was conducted using a completely randomized design (CRD) with a 2 x 5 factorial scheme, two sources of manure (cattle and poultry), five doses (0, 3, 6, 9 and 12 kg m -2 ) and four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 16 publications
1
7
0
2
Order By: Relevance
“…In the peppermint EO, oxygenated monoterpenes constituted 91.2% of the total oil. The composition of EO is similar to previous reports (Costa et al 2013; Ross and ElSohly 1996).…”
Section: Resultssupporting
confidence: 91%
“…In the peppermint EO, oxygenated monoterpenes constituted 91.2% of the total oil. The composition of EO is similar to previous reports (Costa et al 2013; Ross and ElSohly 1996).…”
Section: Resultssupporting
confidence: 91%
“…It is known that the essential oil quantity and quality in raw materials depends on a plant organs proportion, age, climatic conditions, agricultural techniques, extra nutrition, degree of contamination and protection systems. In Brazil, research by Costa et al (2013) with colleagues revealed that various organic amendments sources and influence of doses on plants and essential oil biomass manufacture, changes in menthone, pulegone and menthyl acetate quantitative composition were observed in essential oil chemical composition, although menthol indices were stable. Growth regulators at application on a green leaf differently influence pepper mint essential oil productivity and qualitative characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The quality of the peppermint essential oil has been studied in relation to certain types of nutrients, mineral or organic fertilizers in various researches of Zheljazkov & al (2010) [40], Costa & al (2013) [7] and in relation to the plants age and the harvesting time of the herbs.…”
Section: Resultsmentioning
confidence: 99%